Babaring lelakon; The use of -ing in Javanese genitive constructions - Krauße, Daniel (UI Scholars Hub, 2021)
Two nominals in a genitive construction in Javanese are typically linked by the suffix -é in the low speech level and by -ipun in the high level, both of which are derived from the third person possessive suffix. There is a third suffix which links two nominals, namely -ing, which has so far received little attention in the literature. In this article, I present a syntactic and historical analysis of the suffix -ing. Of particular concern are four types of genitive constructions which permit the use of -ing, as opposed to two constructions where this suffix cannot be used.